The Effect of Reality Therapy on the Level of Anxiety and Depression in Army Wife - Fourida, Ibrahim Nasrul; Sudiyanto, Aris; Fanani, Moh. (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
BACKGROUND: Anxiety and depression, are the most common psychopathological symptoms among army wives living in Kopassus (Indonesian army special force) dormitory, with the prevalence of 15-40%. Proper management with reality therapy for anxious and depressed army wives living in Kopassus dormitory is needed.OBJECTIVE: to determine the effect of reality therapy on anxiety and depression levels in army wives in Kopassus Group 2 dormitory.METHODS: This study was designed as a randomized control trial pretest and post-test two group design. Sampling was done by simple random technique. Thirty subjects were divided into two groups. Control group received regular interview, while experimental group received reality therapy. Respondents were asked to fill out The Lie Minnesota Multiphasic Personality Inventory questionnaire (L-MMPI), biodata, the Taylor Manifest Anxiety Scale questionnaire (TMAS), and the Beck Depression Inventory questionnaire (BDI). The Wilcoxon Rank Test and Mann-Whitney were applied for data analysis, with the significance level of p<0.05.RESULT: The Wilcoxon Rank Test in the TMAS (anxiety) and BDI (depression) showed a significant difference (p<0.05). The Mann-Whitney analysis of the anxiety and depression variables showed a significant difference between the reality therapy group and the control group (regular interview) (p <0.05). The experiment group has a TMAS and BDI score lower than that of the control group.CONCLUSION: The reality therapy is effective to lower the level of anxiety and depression in army wives.